2003
DOI: 10.1016/s0379-6779(02)00910-4
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical excitations in crystalline conjugated polymers

Abstract: We calculate the electronic and optical excitations of crystalline polythiophene and polyphenylenevinylene, using the GW approximation for the electronic self-energy and including excitonic effects by solving the electron-hole Bethe-Salpeter equation. We compare with our earlier calculations on an isolated polythiophene chain and polymer chains embedded in a dielectric medium. Surprisingly, we find for the crystalline calculations optical gaps and exciton binding energies that are significantly smaller than pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Vracko et al applied RPA and TDA to the exciton energies of polyethylene. Rohlfing et al 40 and van der Horst et al 41 applied this method to the exciton states of conjugated polymers and showed that the excitation energies are well comparable with experiments. Kertész applied the intermediate exciton theory to the exciton states of polyacetylene and calculated the exciton energies from electron-hole pair Green's function from semiempirical Hartree-Fock wave function.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Vracko et al applied RPA and TDA to the exciton energies of polyethylene. Rohlfing et al 40 and van der Horst et al 41 applied this method to the exciton states of conjugated polymers and showed that the excitation energies are well comparable with experiments. Kertész applied the intermediate exciton theory to the exciton states of polyacetylene and calculated the exciton energies from electron-hole pair Green's function from semiempirical Hartree-Fock wave function.…”
Section: Introductionmentioning
confidence: 82%
“…A standard method to calculate the exciton states is to use the configuration-interaction singles ͑CIS͒ method, random-phase approximation ͑RPA͒ method, or RPA with Tamm-Dancoff approximation ͑TDA͒. [37][38][39][40][41] In this approach, the Bethe-Salpeter equation for the two-particle Green's function is solved to obtain excitation energies. 31 Another approach to calculate exciton energies is Green's function method.…”
Section: Introductionmentioning
confidence: 99%